Quantitative magnetic resonance imaging to aid clinical decision making in autoimmune hepatitis. (April 2022) - Heneghan, Michael A.; Shumbayawonda, Elizabeth; Dennis, Andrea; Ahmed, Refah Z.; Rahim, Mussarat N.; Ney, Michael; Smith, Loren; Kelly, Matt; Banerjee, Rajarshi; Culver, Emma L.
Summary: Background: In autoimmune hepatitis (AIH), clinical practice and treatment guidelines frequently diverge as a reflection of disease heterogeneity and challenges in achieving standardised care. We sought to explore the utility of multiparametric (mp) MR in patients with AIH, and the impact of this technology on physicians' decision making and intended patient management. Methods: 82 AIH patients, recruited from two sites between June and November 2019 as part of an observational cohort study, underwent non-contrast MRI alongside their standard clinical investigations. Correlations between iron-corrected T1 (cT1) and other markers of disease were investigated alongside the utility of imaging markers to risk stratify patients in biochemical remission. The impact of mpMR on clinical decision making was evaluated using pairwise t-tests. The discriminatory ability of the imaging markers was assessed using area under the receiver operating characteristic curves (AUCs). Findings: cT1 had a significant impact on clinician intended patient management ( p <0.0001). cT1 correlated with ALT ( p  = 0.0005), AST ( p <0.001), IgG ( p  = 0.0005), and liver stiffness ( p <0.0001). Patients in deep biochemical remission ( N  = 11; AST/ALT <50% upper limit of normal [ULN] and IgG <12 g/L) had low cT1, while 7/34 in normal biochemical remission (AST/ALT between 50 and 100% of ULN) had high cT1 and were at risk of disease flare. cT1 measures of disease heterogeneity, ALP and bilirubin made the best predictor of those not in biochemical remission (AUC:0.85). Interpretation: This study investigates the impact of mpMR results on intended clinical management in a real world setting. Findings showed that mpMR demonstrated a significant impact on clinical management of AIH and has the potential to inform patient risk stratification. Funding: This paper presents independent research supported by the Innovate UK grant (104, 915).